2014
DOI: 10.1002/chem.201400241
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Stimuli‐Responsive Organometallic Gels Based on Ferrocene‐Linked Poly(Aryl Ether) Dendrons: Reversible Redox Switching and Pb2+‐Ion Sensing

Abstract: We describe the design, synthesis, and "stimuli-responsive" study of ferrocene-linked Fréchet-type [poly(aryl ether)]-dendron-based organometallic gels, in which the ferrocene moiety is attached to the dendron framework through an acyl hydrazone linkage. The low-molecular-weight gelators (LMWGs) form robust gels in both polar and non-polar solvent/solvent mixtures. The organometallic gels undergo stimuli-responsive behavior through 1) thermal, 2) chemical, and 3) electrochemical methods. Among them, conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 133 publications
0
22
0
2
Order By: Relevance
“…The dendron in the gel phase were initially examined by using optical microscopic techniques 18. 35 The optical microscope images of the gels of 1 a and 1 b obtained from the mixture of DMSO/water with and without thermal treatment were depicted in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dendron in the gel phase were initially examined by using optical microscopic techniques 18. 35 The optical microscope images of the gels of 1 a and 1 b obtained from the mixture of DMSO/water with and without thermal treatment were depicted in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…31 The mechanism of phase transition is identical to that observed during electrochemical oxidation, that is, TTF was oxidized to TTF . + , which results in the repulsion between the MPTTF units to destroy the π–π and S ⋅⋅⋅ S interactions between TTF units, and thereby the gel network collapses 18. Notably, when an equivalent ascorbic acid (Vitamin C, Vc) dissolved in small amount of water was added to the oxidized solution, which was able to reduce TTF .…”
Section: Resultsmentioning
confidence: 99%
“…Reversible sol–gel phase transition could be realized under thermal and electrochemical stimuli. Moreover, these gels showed a specific response to Pb 2+ ions triggering the gel–sol transition, paving the way to an easy detection kit for lead ions with a detection limit close to the ppb level 322. Most recently, Su et al fabricated a multi‐stimuli‐responsive photochromic metal–organic gel responsive to light, heat, water, and anions (Figure b).…”
Section: Multi‐stimuli‐responsive Bulk Gelsmentioning
confidence: 99%
“…Previous results from our group revealed that poly(aryl ether) dendrons linked to pyrene, naphthalene, anthracene, ferrocene, phenothiazine through an acylhydrazone linkage readily form organogels. In order to develop hydrogels based on poly (aryl ether) dendrons, we have attached water soluble PAMAM dendrons with poly(aryl ether) acylhydrazone.…”
Section: Preparation Of Gelmentioning
confidence: 99%